Functional Foods — mat eller medicin? - Rådström, Ann-Louise (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2000)
The food shops and the press in Sweden has recently been overflowed with a new type of food, called Functional Foods. These foods balances on the line between medicine and food and are produced with the intention that the consumers will stay healthy. But, it's difficult for us to choose whether we should go on looking for vegetables and whole-wheat bread or give up and buy the "ready-stuff". It's not just the product we buy, it's a lifestyle, and different sorts of food signals different things depending what the trend is at the moment. It visualizes the need to belong to a group or be defined as a special type of person. It is interesting to look at functional foods, the marketing and the consumers way of dealing with these strange things, ice-cream with oatmeal, juice with calcium or maybe yoghurt full of bacteria. But who is buying this? Maybe the producers have made a new type of food for the already healthy people and failed to create products that "saves the undernourished". These thoughts about functional foods is supposed to be a part of a bigger project about our fast-changing food society where the connection between food and health is strong in many ways.